2014
DOI: 10.1123/jpah.2011-0345
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Active School Transport and Physical Activity, Body Composition, and Cardiovascular Fitness: A Systematic Review of 68 Studies

Abstract: These findings suggest that AST should be promoted to increase PA levels in children and adolescents and that cycling to/ from school is associated with increased cardiovascular fitness. Intervention studies are needed to increase the quality of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
262
4
29

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(320 citation statements)
references
References 112 publications
13
262
4
29
Order By: Relevance
“…The increase in total MVPA for the bicycle train intervention compared with control students was +21.6 minutes/day, which represents more than one third of the recommended daily amount of MVPA. This increase is larger than: (1) the ~7-minute increase in MVPA by a walking school bus program RCT, 6 (2) other previous RCTs on children’s active commuting to school, 23 and (3) general childhood physical activity RCTs in which a systematic review reported increases of ~4 minutes/day of MVPA. 63 As expected, more than 50% of the additional MVPA achieved by the intervention children was due to increases in the before- and after-school periods.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The increase in total MVPA for the bicycle train intervention compared with control students was +21.6 minutes/day, which represents more than one third of the recommended daily amount of MVPA. This increase is larger than: (1) the ~7-minute increase in MVPA by a walking school bus program RCT, 6 (2) other previous RCTs on children’s active commuting to school, 23 and (3) general childhood physical activity RCTs in which a systematic review reported increases of ~4 minutes/day of MVPA. 63 As expected, more than 50% of the additional MVPA achieved by the intervention children was due to increases in the before- and after-school periods.…”
Section: Discussionmentioning
confidence: 66%
“…16 Cycling is more intense than walking 17,18 and may confer greater health benefits, 1922 such as positive improvements in cardiovascular fitness. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Reviewing SHES responses, schools in the initiation phase did not have organized walk-to-school programs and events, and the majority did not allow bikes or scooters on school property. Given the importance of the school trip as a source of physical activity [22], this finding is encouraging in highlighting the critical role schools may play in encouraging and facilitating active school travel while achieving broader public health goals related to children’s physical activity. Greater support for schools in developing and implementing strategies to promote active transportation are warranted.…”
Section: Discussionmentioning
confidence: 95%
“…21 Larouche et al analisaram, em seu estudo de revisão, a associação entre transporte ativo e aptidão cardiovascular, e apontaram que mesmo que se tenha encontrado valores maiores de velocidade em quem faz transporte ativo, esses resultados ou não tem significância estatística ou só tem após estratificação de acordo com a distância do percurso. 23 13 Porcentagem similar foi encontrada por Aarts et al (2013) em seu estudo com crianças holandesas, apesar de haver algumas diferenças de acordo com a idade e a distância da casa, até a escola. 18 Embora nesse trabalho, não se tenha avaliado os motivos que levam as crianças a optarem pelo uso de determinado meio de transporte para se deslocar a escola, há evidências de que entre os principais fatores que influenciam nesta escolha estão os aspectos Tabela 1.…”
Section: Justificación Y Objetivosunclassified